Juridical Analysis Of Approval Of Medical Acts - Bagus Indra; Rudi Hafiz (International Asia Of Law and Money Laundering, 2022)
Approval of Medical Action (informed consent) in health services is a matter that must be done by doctors to patients in terms of legal aspects. For this reason, it is necessary to pay attention to the implementation of the approval of the medical act. So to note also the obstacles and solutions overcome in the implementation of health services to patients, so that there is legal protection for both doctors and patients.